Genetic regions affecting the replication and pathogenicity of dengue virus type 2 - Samune, Yoshihiro; Saito, Akatsuki; Sasaki, Tadahiro; Koketsu, Ritsuko; Srimark, Narinee; Phadungsombat, Juthamas; Yokoyama, Masaru; Kotani, Osamu; Sato, Hironori; Yamanaka, Atsushi; Haga, Saori; Okamoto, Toru; et al. (PLOS Neglected Tropical Diseases, 2024)
Author summary Since the discovery of dengue virus (DENV) in 1907, many people in Latin America, and South and Southeast Asia have been at risk of infection. Analysis of the sequences of viruses isolated in Thailand in 2016 and 2017 revealed the emergence of the Cosmopolitan genotype of DENV type 2 (DENV2), and its co-circulation with the pre-existing Asian-I genotype of DENV2. This co-circulation still exists in Thailand. We noted that there were large differences in the infectious titers between these genotypes, and the focus sizes also differed. In the present study, we analyzed both the in vitro and in vivo characteristics of these viruses using multiple recombinant viruses to determine which viral genetic region is responsible for these differences. We identified a genetic region encoding structural and NS1-NS2B proteins that affects the infectivity, replication, and pathogenicity of the viruses. Our study provides new insights into the transmission of new DENVs, and the interactions between DENV proteins.